RIPK1‐mediated immunogenic cell death promotes anti‐tumour immunity against soft‐tissue sarcoma. Issue 6 (18th May 2020) - Smith, Henry G; Jamal, Kunzah; Dayal, Jasbani HS; Tenev, Tencho; Kyula‐Currie, Joan; Guppy, Naomi; Gazinska, Patrycja; Roulstone, Victoria; Liccardi, Gianmaria; Davies, Emma; Roxanis, Ioannis; Melcher, Alan A; et al.
Abstract: Drugs that mobilise the immune system against cancer are dramatically improving care for many people. Dying cancer cells play an active role in inducing anti‐tumour immunity but not every form of death can elicit an immune response. Moreover, resistance to apoptosis is a major problem in cancer treatment and disease control. While the term "immunogenic cell death" is not fully defined, activation of receptor‐interacting serine/threonine‐protein kinase 1 (RIPK1) can induce a type of death that mobilises the immune system against cancer. However, no clinical treatment protocols have yet been established that would harness the immunogenic potential of RIPK1. Here, we report the first pre‐clinical application of an in vivo treatment protocol for soft‐tissue sarcoma that directly engages RIPK1‐mediated immunogenic cell death. We find that RIPK1‐mediated cell death significantly improves local disease control, increases activation of CD8 + T cells as well as NK cells, and enhances the survival benefit of immune checkpoint blockade. Our findings warrant a clinical trial to assess the survival benefit of RIPK1‐induced cell death in patients with advanced disease at limb extremities. Synopsis: The pathways that initiate and execute immunogenic cell death are complex, genetically encoded, and subject to significant regulation. This study focusses on the possibility to engage RIPK1‐mediated immunogenic cell death for the treatment of soft tissue sarcomas that occur at limb extremities. Inhibition of IAPs via small‐molecule SMAC mimetics potently sensitised extremity malignancies to the standard‐of‐care treatment TNF/Melphalan. Co‐treatment with SMAC mimetics converted non‐immunogenic intrinsic apoptosis to Ripk1‐assisted immunogenic cell death. Ripk1‐induced cell death augmented tumour immune infiltration, delayed tumour growth and prolonged survival. Combination therapy with SMAC mimetics and checkpoint inhibitors further prolonged recurrence‐free survival following isolated limb perfusion‐mediated TNF/Mel treatment. SMAC mimetics improved anti‐tumour immunity of standard‐of‐care treatment for soft tissue sarcomas that occur at limb extremities. Abstract : The pathways that initiate and execute immunogenic cell death are complex, genetically encoded, and subject to significant regulation. This study focusses on the possibility to engage RIPK1‐mediated immunogenic cell death for the treatment of soft tissue sarcomas that occur at limb extremities.